The Shiv Sena and the MQM: A Comparative Perspective. - Schmidt, James. (2017)
Abstract: This thesis explores the respective origins and evolutions of the Shiv Sena and the MQM from a comparative perspective. It examines these two political parties in the context of their respective urban milieus, Mumbai and Karachi, and investigates the extent to which the Indian and Pakistani governments' embrace of economic liberalization as policy from the 1980s onward has empowered these two parties and shaped their respective trajectories. Utilizing party publications, newspapers, government documents, and publications of NGOs, I argue that the Shiv Sena and the MQM adopted the politics of ethnic identity not as an instrument in the service of economic liberalization, but rather as a central component thereof. Juxtaposing the respective evolutions of the two parties, I demonstrate the stylistic and ideological convergence of the two parties which economic liberalization has in part wrought, despite the differing class, ethnic, and religious roots from which the two parties originated.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of History.; Advisor: Ayesha Jalal.; Committee: Kris Manjapra.; Keyword: Asian History.